Recovery model of takaful education plan with additional benefit for parents of learning disabled children - Nurul Zawani Baharazi
Number of learning disabled children in Malaysia were increasing by years. However, lack of exposure, knowledge and awareness cause them to always be mistreat and negleted by the society especially in term of educational needs. Hence, to fill in the gap founded, this study is proposing a new recovery model on existing takaful education plan that made especially to meet the learning disabled children's needs. Takaful was chosen in modelling the education plan to follow the Islamic principle as conventional insurance has been declared to be haram by most muslim scholars. In addition, this recovery takaful education plan also offered special benefits for parent of learning disabled children, as in our concern, the most influenced person around the children with learning disability is their parents. Research data used to estimate the acceptance for new recovery takaful education plan were collected using questionnaires filled in through survey. Six states namely Peri is, Kedah, Kelantan, Terengganu, Negeri Sembilan, and Selangor were chosen to represent three cluster of north, east, and west peninsular Malaysia. The respondents were 115 takaful participants which had at least one child, it was based to the research target population. Structural Equation Modelling (SEM) were used to test the hypothesis of this study by using Statistical Package for Social Science (SPSS) Amos software. Reseach analysis proved that the independent variables (general knowledge of learning disabled, awareness towards nutritional care, and implementing the parental skill) had significantly correlated with dependent variable (public acceptance on new recovery takaful education), meaning that the public had accepted the new recovery takaful education plan to be available in mainstream market. The p-value for the acceptance towards new takaful plan on parenting skill awareness is less than 0.00 I, while on nutritional care awareness is 0.005. This show that the takaful participant agreed with the recovery model offered which provide the additional benefit for the parents of learning disability. In conclusion, this study provides alternative takaful plans to the participant of takaful education which it offers the equality rights to the learning disable people.